2013
DOI: 10.1134/s1995078013010114
|View full text |Cite
|
Sign up to set email alerts
|

Composite materials based on graphene nanoplatelets and polypropylene derived via in situ polymerization

Abstract: Nanocomposites of polypropylene and graphene nanoplatelets were synthesized by in situ polymerization in liquid monomer in the presence of highly effective isospecific homogeneous metallocene catalyst. Microstructure, mechanical, dielectric, and thermal properties of composites are presented. X-ray phase analysis data indicate that graphene nanoplatelets are present in composites as thin flaky particles aggregates, with aspect ratio affected by sonication of reaction mixture. Crystallization temperature of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 22 publications
1
15
0
1
Order By: Relevance
“…Sun 1 , X. Gao 1 , X. He 1 , X. Zheng 1 , I. Skopincev 2 , N. Memetov 3 , A. Tkachev 4 , Z. Zhi 5 of these structures would be observed if the fillers have a large contact surface and aspect ratio, see examples in the previous studies, carbon fiber [10,21], CNTs [17,22] and graphene [19,23]. For example, in work [22] a wide review of works aimed at studying the relationship between the geometric shape of the filler and the structure of the polymer composites was presented.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Sun 1 , X. Gao 1 , X. He 1 , X. Zheng 1 , I. Skopincev 2 , N. Memetov 3 , A. Tkachev 4 , Z. Zhi 5 of these structures would be observed if the fillers have a large contact surface and aspect ratio, see examples in the previous studies, carbon fiber [10,21], CNTs [17,22] and graphene [19,23]. For example, in work [22] a wide review of works aimed at studying the relationship between the geometric shape of the filler and the structure of the polymer composites was presented.…”
Section: Introductionmentioning
confidence: 92%
“…The most effective way to improve the electrical conductivity behavior of CPCs is increasing the concentration of the filler, which leads to a denser arrangement of filler particles in the matrix and simplifies the mechanism of conductivity between them. However, in a certain case, the higher concentration would lead to a critical decrease in the physical and mechanical properties of composite [9,23]. Recently the research studies demonstrated the emergence of new effective methods for organizing filler networks to improve the conductive properties of CPCs.…”
Section: Introductionmentioning
confidence: 99%
“…Solution processing has shown success in other GNP-nanocomposite systems [12,13], however this technique is not applicable to polyolefin-GNP nanocomposites due to the general insolubility of polyolefins. Other fabrication techniques include, nanoparticle surface coating [11], polymerization filling technique [14], Solid State Shear Pulverization [15][16][17], Solid State Ball Milling [18], and in-situ polymerization [19][20][21][22][23].…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…Polyolefin-GNP nanocomposites have recently been prepared via in-situ polymerization, and demonstrated modest increases in linear mechanical properties [19][20][21]23,29]. However, the non-linear mechanical properties of the PNCs in these studies were limited by their relatively low molecular weight (M w < 80,000 g/mol).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation